Dal rilievo laser scanner al modello digitale in VR Dall'acquisizione dello stato di fatto alla realtí virtuale per un'esperienza immersiva unica - Alessandro Novara (mediaGEO soc. coop., 2020)
In a period in which technology is advancing rapidly and even the national business plan (Industry 4.0) is pushing automation, the world of architecture is also changing. New technologies are mature. It is natural now to talk about BIM but what is the correct flow to transform a point cloud into a digital model that can be fully visited in VR? thanks to the use of the Autodesk platform you can take advantage of all the new technologies to achieve this: Infraworks can insert the project created with autodesk revit through three- dimensional maps. Once inserted the model can be animated and analyzed in its real context.